Book Review: Angela Lumezeanu, “Infrastructuri digitale pentru istoria socială. Construirea bazelor de date istorice”, Cluj-Napoca, Mega, 2021, 196 p. - HAIDUC, Alexandru-Augustin (Studia Universitatis Babeș-Bolyai Historia, 2021)
The monograph by Angela Lumezeanu represents a recent addition to the Digital Humanities (DH) research trend developed at Babeş-Bolyai University Cluj-Napoca during the 2010s by the scholars in the field of Humanities who are mostly but not exclusively historians. The author is a Junior Researcher at Babeş-Bolyai University, Centre for Population Studies and software engineer at “George Bariţiu” History Institute of The Romanian Academy in Cluj-Napoca. She has a formal education in both History and Computer Science and has a solid experience working on DH projects, the best-known of which is the Historical Population Database of Transylvania.